Oil palm kernel globulin antihypertensive peptides: isolation and characterization, ACE inhibition mechanisms, zinc-chelating activity, security and stability - Zhang, Liangliang; Pan, Ding; Shao, Lihua; Zheng, Yajun; Hao, Wenhui; Kan, Yu; Cao, Jiawei; Yu, Haotong; Liu, Jing (Frontiers in Pharmacology, 2023)
The oil palm kernel (OPK) expeller is the main byproduct of palm oil, but its utilization is limited. To obtain angiotensin-I-converting enzyme (ACE) inhibition peptides with Zn-chelating capacity, defatted oil palm kernel globulin hydrolysates (DOPKGH) were subjected to Sephadex G-15 gel electrophoresis, reverse-phase high liquid performance chromatography, and UPLC-ESI-MS/MS analysis. Five representative oligopeptides, including Gln-Arg-Leu-Asp-Arg-Cys-Lys (QRLERCK), Leu-Leu-Leu-Gly-Val-Ala-Asn-Tyr-Arg (LLLGVANYR), Arg-Ala-Asp-Val-Phe-Asn-Pro-Arg (RADVFNPR), Arg-Val-Ile-Lys-Tyr-Asn-Gly-Gly-Gly-Ser-Gly (RVIKYNGGGSG), and Glu-Val-Pro-Gln-Ala-Tyr-Ile-Pro (EVPQAYIP), without potential toxicity and allergenicity, were identified in DOPKGH. Of these, only EVPQAYIP showed both ACE-inhibitory activity (IC50: 102.75 μmol/L) and Zn-chelating capacity (11.69 mg/g). Molecular docking and inhibition kinetics showed that EVPQAYIP was a competitive inhibitor of ACE because it could bind to Glu384, Lys511, and Gln281 (belonging to the central S1 and S2 pockets, respectively) of ACE. Moreover, EVPQAYIP affects zinc tetrahedral coordination in ACE by binding to Glu411; the amino and carboxyl groups of EVPQAYIP chelate with zinc ions. During gastrointestinal digestion, the ACE inhibitory activity of EVPQAYIP was relatively stable. Additionally, EVPQAYIP enhanced zinc stability in the intestine and exerted antihypertensive effects in spontaneous hypertensive rats. These results suggest the potential application of OPK peptides as ingredients in antihypertensive agents or zinc fortification.